2020
DOI: 10.1177/0284185120902389
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of CT and the use of GI contrast material for detection of hollow viscus injury after penetrating abdominal trauma. Experience from a level 1 Nordic trauma center

Abstract: Background Use of gastrointestinal (GI) contrast material for computed tomography (CT) diagnosis of hollow viscus injury (HVI) after penetrating abdominal trauma is still controversial. Purpose To assess the sensitivity of CT and GI contrast material use in detecting HVI after penetrating abdominal trauma. Material and Methods Retrospective analysis (2013–2016) of patients with penetrating abdominal trauma. Data from the local trauma registry, medical records, and imaging from PACS were reviewed. CT and surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 22 publications
3
13
1
Order By: Relevance
“…The assessment of agreement between the two investigators in the initial screen of 50 studies demonstrated Cohen's kappa of 0.81. Ultimately, 12 studies published between 2004 and 2020 with a total of 1,287 patients with penetrating abdominopelvic injury (389 with confirmed bowel, mesenteric, or other abdominopelvic injury) were included (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Two studies had been excluded due to overlapping patient samples (33,34) with an included study (21).…”
Section: Study Demographics and Risk Of Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…The assessment of agreement between the two investigators in the initial screen of 50 studies demonstrated Cohen's kappa of 0.81. Ultimately, 12 studies published between 2004 and 2020 with a total of 1,287 patients with penetrating abdominopelvic injury (389 with confirmed bowel, mesenteric, or other abdominopelvic injury) were included (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Two studies had been excluded due to overlapping patient samples (33,34) with an included study (21).…”
Section: Study Demographics and Risk Of Biasmentioning
confidence: 99%
“…Two studies had been excluded due to overlapping patient samples (33,34) with an included study (21). The enteric contrast group included seven studies reporting on 506 patients with penetrating injury (124 with confirmed bowel, mesenteric, or other abdominopelvic organ injury) (21,22,24,27,29,30,32), while the nonenteric contrast group included six studies reporting on 781 patients with penetrating injury (265 with confirmed bowel, mesenteric, or other abdominopelvic organ injury) (23,25,26,28,31,32).…”
Section: Study Demographics and Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations